Habit, Self-Organization, and Abduction - de Andrade, Ramon S. Capelle; Broens, Mariana Claudia [UNESP]; D’Ottaviano, Itala M. Loffredo; Gonzalez, Maria Eunice Quilici [UNESP] (Springer Nature, 2014)
In this paper we discuss the hypothesis of Dascal (Artificial intelligence as epistemology? In: Villa Nueva E (ed) Information, semantics and epistemology. Blackwell, Oxford, pp 224–241, 1990) according to which the main characteristic of intelligence is the ability to adapt pragmatically to changes in the context in which one is immersed. Our investigation is an inquiry into the role played by habits, in order to establish criteria according to which agents act in the world in reasonable and relevant ways. To begin with, we investigate the logical form of habits, focusing on the distinction between “rational habits” and “crystallized habits” (“degenerated habits”), and their function in the structuring of actions. We argue that habits manifest themselves in terms of a hypothetical prescription: If A (a circumstance), then B (a behavior). Our hypothesis is that habits can be transformed into abilities by means of processes of secondary self-organization that involve the dynamics of rupture, acquisition, and improvement of previous habits. More specifically, we suggest that abilities, characterized as habits that have been refined or perfected, involve a process of secondary self-organization which can be triggered by (a) the perception of (an agent’s own) habitual behavior and the recognition (by the agent) of the necessity of altering part of this behavior and (b) experience of a doubt that may initiate rational abduction. Furthermore, we adapt the notion of abductive reasoning, as defined by Peirce (In: Hartshorne C, Weiss P, Burks AW (eds) Collected papers of Charles Sanders Peirce, vols 1–8. Harvard University Press, Cambridge, MA, 1958), to deal with the creation of hypotheses of conduct and, in particular, the transition from the experience of a doubt to the acquisition of a habit (understood as a readiness to perform an action).
Keywords: Abductive reasoning; Habits; Self-organization